Rhenium-188 Production in Hospitals, by W-188/Re-188 Generator, for Easy Use in Radionuclide Therapy. (9th April 2013) - Argyrou, Maria; Valassi, Alexia; Andreou, Maria; Lyra, Maria
Abstract : Rhenium-188 (Re-188) is a high energyβ -emitting radioisotope obtained from the tungsten-188/rhenium-188 (W-188/Re-188) generator, which has shown utility for a variety of therapeutic applications in nuclear medicine, oncology, and interventional radiology/cardiology. Re-188 decay is accompanied by a 155 keV predominant energyγ -emission, which could be detected byγ -cameras, for imaging, biodistribution, or absorbed radiation dose studies. Its attractive physical properties and its potential low cost associated with a long-lived parent make it an interesting option for clinical use. The setup and daily use of W-188/Re-188 generator in hospital nuclear medicine departments are discussed in detail. The clinical efficacy, for several therapeutic applications, of a variety of Re-188-labeled agents is demonstrated. The high energy of theβ -emission of Re-188 is particularly well suited for effective penetration in solid tumours. Its total radiation dose delivered to tissues is comparable to other radionuclides used in therapy. Furthermore, radiation safety and shielding requirements are an important subject of matter. In the case of bone metastases treatment, therapeutic ratios are presented in order to describe the efficacy of Re-188 usage.